Sedimentology and Geochemistry of the Upper Permian Linghao Formation Marine Shale, Central Nanpanjiang Basin, SW China - Gu, Yifan; Hu, Dongfeng; Wei, Zhihong; Liu, Ruobing; Hao, Jingyu; Han, Jing; Fan, Zhiwei; Jiang, Yuqiang; Wang, Yansong; Xu, Qidi (Frontiers in Earth Science, 2022)
The Upper Permian Linghao Formation marine shale and contemporaneous transitional shale are the most potential shale gas targets in the Nanpanjiang basin, which is characterized by considerable TOC content, wide distribution, and considerable shale thickness. On the basis of division in Linghao Formation, petrographic, mineralogical, and high-resolution geochemical analyses were integrated to reveal the sedimentary environment including paleoproductivity, paleoredox conditions, detrital influx, paleoclimate, and the paleosalinity. There are two organic-rich shale intervals in Linghao Formation, which are Ling 1 member and the lower Ling 3 member. The lower Ling 1 is dominated by deep-water shelf facies, which are characterized by high TOC value (0.93%–6.36%, avg. 2.43%), high detrital influx proxies (Zr, 746–1508 ppm, avg. 1093 ppm; Ti, 19278–128730 ppm, avg. 16091 ppm), relatively warm–humid paleoclimate condition (CIA*, 75.94-91.90, avg. 82.26), low paleosalinity proxies (Sr/Ba, 0.13-0.34, avg. 0.22), and high paleoproductivity (P/Al (10−2), 1.06-2.06, avg. 1.63; Mn/Ca (10−3), 27.37-291.69, avg. 128.07). Detrital influx including gravity flow plays a critical role in the enrichment of organic matter. The sedimentary environment of upper Ling 1 and lower Ling 3 is the same as that of lower Ling 1. Unlike lower Ling 1, these intervals are characterized by low detrital influx proxies, moderate weathering, and relatively high paleosalinity proxies. The volcanic ash of Emei volcanism and felsic volcanism in South China plays a critical role in the enrichment of organic matter in upper Ling 1 and lower Ling 3, respectively. The sedimentary models for Linghao Formation organic-rich shale can reveal factors controlling the enrichment of organic matter.